Aluminosilikat Berpotensi Menekan Gangguan Reproduksi Mikotoksin Zearalenon Berdasarkan Pengamatan Jumlah Folikel dan Ekspresi Caspase-9 Ovarium - Purnama, Muhammad Thohawi Elziyad; Mustofa, Imam; Suprayogi, Tri Wahyu; Samik, Abdul; Prastiya, Ragil Angga; Saputro, Amung Logam (Jurnal Veteriner, 2017)
Zearalenone is a resorcylic acid lactone produced by fungal Fusarium graminearum in contaminated edible grains and can cause reproduction disorder in animals by binding to estrogen receptors on target cells. The aim of this study was to assess the potential use of aluminosilicates as mycotoxin binders to eliminate the adverse effect of zearalenone by examining the number of follicles and caspase-9 expression in the ovary of mice. The study adopted a completely randomized simple design using 20 mices which were randomly divided into five group each of which consisted of four mices. Five treatment groups consisted of K+ (without zearalenone and aluminosilicates); K- (treated with zearalenone 0.1 mg/mice/day); P1 (treated with zearalenone 0.1 mg/mice/day and aluminosilicates 0.5 mg/mice/day); P2 (treated with zearalenone 0.1 mg/mice/day and aluminosilicates 1 mg/mice/day); and P3 were treated with zearalenone 0,1 mg/mice/day and aluminosilicates 2 mg/mice/day) with gastric tube daily for 10 days. The data obtained from this study were analyzed by analysis of variance and proceeded with Duncan test. The result showed that the primary follicles, secondary follicles, tertiary follicles and de Graaf follicles increased significantly on P3 treatment group. Caspase-9 expressions decreased significantly in all of aluminosilicates groups as compared to positive control. The treatment of mice with zearalenone and aluminosilicates increases the number of follicles and decreased caspase-9 expression in the ovary of mice. ABSTRAK Zearalenon merupakan senyawa resorcylic acid lactone yang diproduksi oleh jamur Fusarium graminearum dan dapat mengakibatkan gangguan reproduksi pada ternak dengan membentuk ikatan pada reseptor estrogen. Penelitian ini bertujuan untuk menguji potensi aluminosilikat terhadap mencit yang telah dipapar zearalenon pada aspek jumlah folikel dan ekspresi caspase-9 organ ovarium. Penelitian ini menggunakan 20 ekor mencit yang dibagi menjadi lima kelompok perlakuan dengan masing-masing empat ulangan, yakni K+ tanpa dipapar zearalenon dan aluminosilikat; K- dosis zearalenon 0,1 mg/ekor/hari; P1 dosis zearalenon 0,1 mg/ekor/hari dan aluminosilikat 0,5 mg/ekor/hari; P2 dosis zearalenon 0,1 mg/ekor/hari dan aluminosilikat 1 mg/ekor/hari; P3 dosis zearalenon 0,1 mg/ekor/hari dan aluminosilikat 2 mg/ekor/hari dengan sonde lambung selama sepuluh hari. Data hasil skoring dan perhitungan dianalisis dengan sidik ragam dan dilanjutkan dengan uji Duncan. Hasil penelitian menunjukkan bahwa jumlah folikel primer, sekunder, tersier dan de Graaf pada P3 terjadi peningkatan yang signifikan. Ekspresi caspase-9 ovarium menunjukkan penurunan pada semua perlakuan aluminosilikat. Simpulan penelitian ini adalah mencit yang dipapar zearalenon dan kemudian diberi aluminosilikat mengalami peningkatan jumlah folikel dan penurunan ekspresi caspase-9 pada organ ovarium.